Association between skin manifestations and glycemic control in patients with type 2 diabetes mellitus - Umičević Šipka, Sanja; Balaban, Jagoda; Bijelić, Radojka (Vojnosanitetski pregled, 2021)
Background/Aim. Diabetes mellitus (DM) can be associated with numerous skin diseases. This study aimed to determine the pattern and incidence of skin manifestations in patients with type 2 DM and their link to glycemic control. Methods. This cross-sectional study was conducted at the Skin and Venereal Diseases Clinic, University Clinical Centre of the Republic of Srpska in Banja Luka, Bosnia and Herzegovina, from January 2016 to January 2018. Adult patients of both genders suffering from type 2 DM and cutaneous manifestations participated in the study. Glycemic control was assessed according to the values of glycated hemoglobin (HbA1c) of 7%. Results. The mean age of 105 study participants (46% male and 54% female) was 68.4 ± 10 years, while the mean HbA1c was 8.3 ± 1.6%. Unsatisfactory glycemic control was found in 74.3% of patients with the mean HbA1c at 8.9 ± 1.4%, while satisfactory glycemic control was found in 25.7% of patients, with the mean HbA1c at 6.7 ± 0.2% (p < 0.001). Infections were the most frequent skin diseases (43.9%). Bacterial infections were most common (26.7%), followed by fungal infections (24.8%), xerosis (17.1%), psoriasis (15.2%), fibroma molle (14.3%), diabetic ulcer (7.7%), prurigo (6.7%), and stasis dermatitis (5.7%). Other skin manifestations were found at a lower rate. A significant association was found between unsatisfactory glycemic control and skin infections (p = 0.009). Conclusion. The most common skin manifestations in patients with type 2 diabetes are infections. They occurred more often in patients with unsatisfactory glycemic control.